ANALISIS KELAYAKAN USAHATANI PADI ORGANIK DAN KONVENSIONAL DI KECAMATAN MOJOGEDANG KABUPATEN KARANGANYAR - Sholihah, Efi Nikmatu; Saputro, Avisema Sigit; Nisa', Hanifah Uswatun (AGRIBIOS, 2024)
Rice farming is the dominant farming business in Java, one of which is Central Java. Rice is still the primadonna commodity because the staple food of most Indonesian people is rice. Currently, there is starting to be a shift from previously conventional farming techniques to organic farming to maintain soil fertility and environmental safety. This research aims to analyze the income and feasibility of organic rice farming and conventional rice farming in Mojogedang District, Karanganyar Regency and was carried out in June-August 2023. This research was carried out using a quantitative approach and descriptive analysis. The research location was determined purposively in the Tani Mulyo 1 Group, Mojogedang District, Karanganyar Regency, involving 25 organic rice farmers and 25 conventional rice farmers. This research uses cost, revenue, income analysis, and also feasibility analysis using the R/C ratio and Break Event Point (BEP). The results of the analysis show that the total cost of organic rice farming is IDR. 9,960,600,- and costs for conventional rice farming are IDR. 10,117,375,-. Average revenue from organic farming is Rp. 47,094,000,- and the average revenue from conventional rice farming is Rp. 40,414,400. Based on these results, the difference between revenues and costs is known so that the income obtained in organic rice farming is Rp. 37,133,400,- and conventional rice farming income is Rp. 30,297,025,-. The R/C ratio value for organic rice farming is 4.73 and for conventional rice farming is 3.99. Based on this analysis, it can be concluded that organic rice farming and conventional rice farming are both feasible to run, but organic rice farming will provide a higher level of profit.